Virulence factors of Pseudomonas aeruginosa and immune response during exacerbations and stable phase in bronchiectasis - Roberto Cabrera; Nona Rovira-Ribalta; Anna Motos; Leticia Bueno-Freire; Nil Vázquez; Alba Soler-Comas; Victoria Alcaraz-Serrano; Rubén López-Aladid; Laura Muñoz; Jordi Vila; Antoni Torres; Laia Fernández-Barat (Scientific Reports)
Abstract The study of key Pseudomonas aeruginosa (PA) virulence factors, the molecular basis of pathogenicity, as well as their correlation with the immune response during exacerbations in patients with non-cystic fibrosis bronchiectasis can help to identify novel targets and biomarkers for clinical management. The objective was to compare P. aeruginosa virulence and the patient’s immune response during stable phases and exacerbations of bronchiectasis. We used polymerase chain reaction (PCR) and real-time quantitative PCR (qRT-PCR) to perform molecular characterization of the genomic islands and virulence genes present in 42 P. aeruginosa strains obtained from the sputum of patients with bronchiectasis during stability and exacerbations. Immunoglobulin (Ig) and interleukin (IL) levels in 32 serum samples were analyze by ELISA and Luminex assay. A greater presence of the conjugative element pKLC102, specific virulence genes (exoS, exoY) and pyoverdine production characterize the P. aeruginosa strains obtained during exacerbations. The expression levels of type III secretion system (exoS, exoY) showed an important role in the humoral immune response during exacerbations. Exacerbations were associated with high levels of IL-6. The presence of specific genomic islands, virulence genes, and increased IL-6 levels provide an accurate characterization on bronchiectasis exacerbations. These targets could be useful in the prevention, management and treatment of these exacerbations.